(3JCSjS GddZIs - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdnqSnerQnbrfOj, CHh GddjK, GdedbH HEeGe GdgOi , J (B373 (3g`s
(3ChdgG (B:s
(3GdGHO heYfGgG dGJJJNPhG ef HOGNd HhGWf CehQce ef Ohfce Gi ef ZjQce s
(3BNQgG (B:s
(3hef Pdc GdNHQ GdhGQO ai LhGR GdHfGA Ydi eGeVi ef UdhJg ef GdMOK GdSGHb bHdI CUMGHfG dCfg hQO eNGdakG dbjGS GdGUhd hGddg CYde HGdUhGH Je JCSjS Gdabg dCHi GddjK QMeg Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdGScfOQjI (B(1792(3O(B) s
Keywords: (3GddZIs